Workforce Management in the Era of Artificial Intelligence— A Critical Review of Artificial and Emotional Intelligence for Employee: Engagement with E-Human Resource Management - Mishra, Priya Kumari (Madhesh Journal of Interdisciplinary Research, 2026)
The book Artificial and Emotional Intelligence for Employee Engagement with E-Human Resource Management, authored by Dr. Anjay Kumar Mishra, Dr. J. Nirubarani, Dr. P. Radha, Mrs. R. Priyadharshini, and Dr. Shila Mishra, presents research-driven perspectives across four sections. This paper reviews Chapter Four on workforce management following class discourse and underlines that every chapter of the book should be discussed chapter-wise and reviewed as an audiobook to broaden access and pedagogical use. Book explores how AI and emotional intelligence (EI) integrate within e HRM to improve workforce planning, administration, and employee self-service. It outlines workforce management practices, their benefits, and administrative processes enhanced by predictive analytics, automated scheduling, and digital self-service platforms. The authors examine how AI tools support diverse needs while EI-informed leadership and interpersonal practices mitigate emotional labor and strengthen engagement. Special attention is given to diversity, harassment prevention, and inclusive policy design, highlighting algorithmic bias risks and data-privacy concerns. The chapter recommends governance frameworks, EI training for managers, and participatory implementation strategies to ensure ethical, human-centered adoption. Illustrative cases and classroom reflections demonstrate practical applications across organizational contexts, offering actionable guidance for scholars and practitioners.